Analisis Input Output Kabupaten Bandung Berdasarkan Tabel Input Output Jawa Barat - Adeliya Sanya Lenita; Teti Sofia Yanti (UNISBA Press, 2022)
Abstract. Input-output analysis is an analysis based on the results of the economy in a region by looking at the interrelationships between economic sectors in the region as a whole. Bandung Regency is one of the regions that has positive economic growth. In this study, changes in the structure of the economy will also look at which sectors are the priority in economic development in Bandung Regency using input-output analysis. There are 3 analysis that the author uses in this thesis, namely location quotient, multiplier analysis, and shift share analysis. The results obtained are 6 basic sectors, namely the Mining and Quarrying sector; Processing Industry sector; Real Estate; Company Services; Education Services; Health Services and Social Activities. There are 14 relatively more advanced sectors in Bandung Regency when compared to the same 14 sectors in West Java province. Abstrak. Analisis input-output merupakan analisis yang didasarkan pada hasil perekonomian di suatu wilayah dengan melihat keterkaitan antar sektor ekonomi di wilayah tersebut secara keseluruhan. Kabupaten Bandung merupakan salah satu wilayah yang memiliki pertumbuhan ekonomi yang positif. Dalam penelitian ini akan dilihat perubahan struktur perekonomian juga melihat sektor mana yang menjadi prioritas dalam pembangunan ekonomi di Kabupaten Bandung menggunakan Analisis input-output. Ada 3 analisis yang penulis gunakan dalam skripsi ini yaitu location quotient, analisis angka pengganda, dan analisis shift share. Didapatkan hasil 6 sektor basis yaitu sektor Pertambangan dan Penggalian; sektor Industri Pengolahan; Real Estate; Jasa Perusahaan; Jasa Pendidikan; Jasa Kesehatan dan Kegiatan Sosial. Terdapat 14 sektor yang relatif lebih maju di Kabupaten Bandung jika dibandingkan dengan 14 sektor yang sama di provinsi Jawa Barat.